Eksistensi Perilaku Lgbt Akibat Penayangan Drama Boys Love Dalam Sudut Pandang Teori Psikoseksual - Tauzia Harari; Ati Kusmawati; Nabila Ayu Dzuhri Rahmah; Febriyani Mufidatul Adha (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
One of the most powerful weapons from the LGBT group today is the drama - drama and film - film they produce, this research is to provide a new view, of how the boys love play can affect the existence of the LGBT group in our midst - and how psychosexual theory views the phenomenon, whether it becomes a basis for a person's sexual orientation to be lesbian, Gay or bisexual. The methods used were qualitative research and literary studies. This approach was chosen because researchers want to explain or describe in detail the phenomena occurring in society, in this case the thought structure experienced by audiences in the drama